TASP1 Promotes Proliferation and Migration in Gastric Cancer via EMT and AKT/P-AKT Pathway - Xue-Mei Wan; Xue-Lei Zhou; Yong-Jun Du; Hui Shen; Zhengxia Yang; Yanhong Ding (Journal of Immunology Research)
Threonine aspartase 1 (TASP1) was reported to function in the development of cancer. However, the regulatory mechanism of TASP1 in gastric cancer (GC) remains unclear. In this study, we determined the expression of TASP1 in tissues of GC patients, GC cells by qRT-PCR, and western blot and assessed the relationship between TASP1 and GC cell proliferation and migration via CCK-8 and transwell assay. It was found that the expression of TASP1 in GC tissues or GC cell lines was significantly higher than that in normal adjacent tissues or normal cells. The proliferation and migration of GC cells were inhibited upon TASP1 knockdown. Mechanism investigation revealed that TASP1 promoted GC cell proliferation and migration through upregulating the p-AKT/AKT expression. TASP1 induced GC cell migration via the epithelial -mesenchymal transition (EMT) pathway. In conclusion, TASP1 promotes GC progression through the EMT and AKT/p-AKT pathway, and it may serve as a new potential biomarker and therapeutic target for GC.